2016
DOI: 10.1155/2016/8048457
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Desire, Partner Serodiscordance, and Partner HIV Disclosure among Reproductive Age HIV-Infected Women in an Urban Clinic

Abstract: Women comprise 25% of the US HIV epidemic, with many women of reproductive age. There is a need for providers to address the reproductive needs and desires of women with HIV given that effective antiretroviral therapy has transformed HIV into a chronic disease. This cross-sectional study shows high rates of partner serodiscordance (61%) and moderate HIV disclosure to partners (61%). Patients surveyed reported practitioners discuss condoms (94%) and contraception (71%) more often than pregnancy desire (38%). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
2
10
0
1
Order By: Relevance
“…The reproductive desire of participants’ partners was associated with the outcome investigated, as found in other studies [ 13 , 25 , 35 ]. Finocchario-Kessler et al [ 29 ] emphasized that in relationships, children are highly valued for the emotional fulfillment they provide to the parents and for the connection generated between the couple.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The reproductive desire of participants’ partners was associated with the outcome investigated, as found in other studies [ 13 , 25 , 35 ]. Finocchario-Kessler et al [ 29 ] emphasized that in relationships, children are highly valued for the emotional fulfillment they provide to the parents and for the connection generated between the couple.…”
Section: Discussionsupporting
confidence: 74%
“…In Asia, one study found a prevalence of 34.0% in Iran [ 34 ]. In North America, prevalence ranging from 25.8% in Canada to 44.0% in the United States has been estimated [ 16 , 34 , 35 ]. These studies have reported differing results, which may be associated to differences in geographical location, cultural factors, prevalence of determinants, and methodological differences applied in each investigation [ 16 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study of PLWH with a partner living without HIV/HIV unknown status partner reported a prevalence of 58% [66]. Regarding WLWH, the three studies found percentages varying from 32% to 55% [25,68,69].…”
Section: Prevalence Of Fertility Desires/intentionsmentioning
confidence: 97%
“…Three studies included both members of the dyad [6,65,67], and the number of serodiscordant couples ranged from 11 to 143 (M = 68; SD = 67.82). In the three studies with WLWH in a serodiscordant relationship, they were the index partner [25,68,69]. In the three studies that included both members of the dyad, the man was the index partner [6,65,67].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation